2021
DOI: 10.1016/j.amjsurg.2020.12.046
|View full text |Cite
|
Sign up to set email alerts
|

The lasting footprint of COVID-19 on surgical education: A resident and attending perspective on the global pandemic

Abstract: Background The COVID-19 pandemic has impacted surgical training nationwide. Our former curricula will likely not return, and training will need to adapt, so we are able to graduate residents of the same caliber as prior to the pandemic. Methods A survey evaluating perceptions of changes made in surgical training was conducted on surgery residents and attendings. Results Disaster medicine training has become more relevant and 85% residents and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 38 publications
(36 reference statements)
0
7
0
2
Order By: Relevance
“…Incorporating concise and impactful instructional videos prior to surgery into a trainee’s preoperative case preparation may augment the trainees’ learning curve and ultimately contribute to improved safety measures. 12,13…”
Section: Preparationmentioning
confidence: 99%
“…Incorporating concise and impactful instructional videos prior to surgery into a trainee’s preoperative case preparation may augment the trainees’ learning curve and ultimately contribute to improved safety measures. 12,13…”
Section: Preparationmentioning
confidence: 99%
“…The 2020 COVID-19 pandemic has had an impact on all aspects of general surgery training. Residency conferences and didactics moved to online platforms, rotations were canceled to reduce viral exposure, and non-urgent elective cases were delayed or rescheduled [7,8,27]. A concern for skills decay with the decrease in opportunities for procedural training emerged as a result.…”
Section: Resident Education During Covidmentioning
confidence: 99%
“…Surgical training has been uniquely impacted both operatively and nonoperatively. Residents had to quickly adapt to a 'new normal' as many elective surgeries were canceled, resident lectures and conferences were moved to online platforms, and rotations were canceled or shortened to redistribute the workforce [7,8]. This pandemic has demonstrated that surgical education needs to adapt to train tomorrow's surgeons.…”
Section: Introductionmentioning
confidence: 99%
“…However, there have been no further studies to validate this teaching method. One recent survey [ 34 ] found that many residents view publicly available material on the internet, which is often not peer-reviewed, potentially industry-driven and unregulated [ [35] , [36] , [37] ]. Access to Society webpages and education portals that offer peer-reviewed videos of higher quality may be limited due to cost or subscription requirements.…”
Section: Introductionmentioning
confidence: 99%